Subjetividad social, sujeto y representaciones sociales (2008)
This paper discusses some of the challenges concerning development social representations in current psychology. As with any theoretical construction capable of shedding light on new aspects in scientific thought, the concept of social representation has expanded itself throughout authors who use it with different theoretical and methodological bases. The concept of subjectivity, from a historical cultural standpoint, is introduced in the discussion concerning the current alternatives for the development of social representation. From this framework, subjectivity is completely redefined, gaining a new meaning as part of a completely new theoretical system. Starting from this definition, subjectivity is understood not as exclusively individual phenomena, but as an important side of any social phenomena. The concept of social subjectivity is discussed in its consequences for the social representation's development. This discussion involves social subjectivity, subject and social representation into a complex and dynamic system.